Pengaruh Inovasi Promosi Media Sosial Instagram dan Tiktok untuk Menarik Pelanggan Baru pada Bube Boba Café - Nirwani, Sekar; Lubis, Nurul Wardani; Amalia, Delvi Dede; Sembiring, Ananda Amelia; Ardana, Tasya Novi (As-Syirkah: Islamic Economic & Financial Journal, 2024)
In today’s digital age, social media has become one of the most effective tools for marketing a variety of, including the food and beverage industry. Platforms like Instagram and TikTok provide a great opportunity for to interact directly with their customers like Bube Boba Cafe. As a result, BubeBoba Cafe must maximize both of these platforms in its marketing strategy. The type of research used is qualitative descriptive method. This method is used to provide a more detailed description of the impact of Instagram and TikTok's social media promotion innovations on the recruitment of new customers at Bube Boba Cafe. The sample used in this study is a BubeBoba Cafe customer who uses social media Instagram and tikTok to learn information about products and promo cafes. The data collection technique used in this study is with interviews and study of libraries or written sources such as books, previous research, papers, data collected and then analyzed to find out the impact of Instagram and TikTok social media promotion innovations on the recruitment of new customers at Bube Boba Cafe. Data analysis is carried out using descriptive qualitative analysis techniques to obtain a more detailed description and detail of the results of the research. To run a strategy using social media touch. Bube Cafe uses promotional tools in carrying out its promotional activities, as follows: 1. Advertising The advertising media on the social media of TikTok is the tikTok ads, from which there are several types of ads such as pre-roll asd is the video ad that is started when the user opens tiktok, in-feed ads is the advertising video that appears when the users of tiktok menscroll feed, promoted hastag challenges is video that encourages the users to use special tags, and last branded effects is the filter of special effects to be used by the creators of content in video, these effects are similar to the filters that exist in snapchat and instagram but which is the differentiator is this filter displays special information. 2. Direct marketing is like making interactive videos.